Cardiovascular disease risk factors and anthropometry features among seemingly healthy young adults - Viskasari P. Kalanjati; Rury T. Oktariza; Bambang E. Suwito; Krisnawan A. Pradana; Dzanuar Rahmawan; Abdurachman Abdurachman (Intelektual Pustaka Media Utama, 2021)
We explored association between the levels of total cholesterol (TC) and uric acid (UA) to the middle upper arm circumference (MUAC), waist circumference (WC) and hip circumference (HC) amongst seemingly healthy university students in Kediri, Indonesia aged 17-23 years (n=150); no history of major previous diseases were found (i.e. metabolic syndrome). TC and UA measured from the capillary blood; standardised anthropometry measurements were done by trained medical doctors. Correlation, linear regression, independent t-test or Mann-Whitney analysis were performed with the level of significance of p<0.05. We found higher TC (p=0.053), UA (p<0.001), MUAC (p=0.009), HC (p=0.865) and WC (p=0.001) among males than among females. TC was significantly correlated to the UA with prevalence of hypercholesterolemia of 46.7% and hyperuricemia of 30% of all participants. All anthropometry was significantly correlated to the TC and UA among males (p<0.001); TC and UA were strongly corresponded to all anthropometry parameters among males. Hypercholesterolemia and hyperuricemia could be found amongst the seemingly healthy young adults in Indonesia; among males these are strongly correlated to the higher MUAC, WC and HC. Daily physical activity and proper healthy diet might help to decrease these cardiovascular disease risk factors.